MADURESE MILLENNIAL STUDENTS’ ANXIETY IN LEARNING ENGLISH - Mohammad Amiruddin; Tanti Suparti (Jurusan Sastra Indonesia, 2018)
This study is to find out the models of Madurese millennial students’ anxiety and thefactors causing the Madurese millennial students’ anxiety in learning English. Thisresearch is a qualitative research by using descriptive case study. The participants ofthe study are Madurese millennial students at English Department of MaduraUniversity. Observation and interviews with Madurese millennial students wereconducted to get the data of the models and factors causing their anxiety. The resultsof the study indicate that Madurese millennial students experience two kinds ofanxiety models those are interference and deficit models. Interference models aremore dominants than deficit models. The teachers, friends, and abilities of Maduresemillennial students are the factors causing their anxiety in learning English. Theteachers are the first factors causing their anxiety. Their abilities in English become thesecond factor. However, it rarely happens to Madurese millennial students feelnervous when they are communicating with their peers. The communication inEnglish become natural with no anxiety when they with their friends. Therefore, itimplies that the teachers should propose the classroom activities providing facilitiesand helping the students to get meaningful input in English in order to overcomefrom their anxiety.